Clinical Efficiency and Safety of Riamilovir for Treating Patients with SARS-CoV-2 Infection - K. V. Kasyanenko; O. V. Maltsev; K. V. Kozlov; I. I. Lapikov; N. I. Lvov; V. S. Sukachev; K. V. Zhdanov; P. V. Sorokin; A. K. Ratnikova (Антибиотики и Химиотерапия, 2021)
Aim. The study evaluates clinical effectiveness and safety of etiotropic antiviral medications with a direct mechanism of action (Riamilovir, Ribavirin, Umifenovir) for the treatment of moderate SARS-CoV-2 infection in adults. Materials and methods. The study used the data from 59 health records of patients with moderate PCR-confirmed SARS-CoV-2 infection. Control group included 29 patients treated with 1250 mg Riamilovir off-label per day for 5 days (250 mg 5 times a day), comparison group consisted of 30 patients, who received 800 mg Ribavirin and Umifenovir per day for 5 days. The effectiveness of the medications was assessed by the duration and severity of general infectious and respiratory syndromes, anosmia and ageusia, as well as the oxygen content in the blood, the timing of SARS-COV-2 virus elimination from the body according to the results of control studies of nasopharyngeal swabs using the PCR method and dynamics of blood tests results. Results. A statistically significant decrease in the duration of fever, cough, and anosmia and a more rapid elimination of the virus from the body were noted in the group of patients receiving Riamilovir. Decreased levels of non-specific inflammatory markers in blood serum, as well as normal values of liver enzymes were observed in control group during therapy, as opposed to the comparison group. No serious adverse events were noted when using the medication. Conclusion. Nucleoside analogue medication Riamilovir showed good effectiveness and safety profile in adult patients with moderate SARS-CoV-2 infection.